RESPON MASYARAKAT TERHADAP KEBERADAAN CAFÉ REMANG-REMANG DI BUKIT BETABUH DESA KASANG KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Dirman "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study is to provide an overview of the public response to the presence of café remang-remang and give a description of the factors that make café remang-remang remained in existence until today. Basic research is the survey in desa kasang. As for the type of research is descriptive quantitative research that is working with numbers in subsequent statistical analysis used in describing the reality. Collecting data through obsertion. And direct interview to the respondents. Sampling techniques in this study using methods purposive sampling. Taking samples 42 respondents (10.29%) from 408 head of family. Data collected from the research results were processed using frekuansih table with presentation. Research shows that most people assume the existence of a dimly lit café is negative and the impact on the younger generation. But here relatively negative negative light because no decisive acion from the government or society to café remang-remang which had stood for a long time. Whereas the factors that make the café remang-remang remained in existence until now in the weak level of religion, low levels of education, lack of skills, economic status, and lack of social control. Among the factors that most makes eksis café remang-remang economic factors and social control. To reduce the presence of café remang-remang which exist in kasang expected to community, government and community leaders would be willing to supervise and provide decisive action to those who founded the café remang-remang, and provides guidance to adolescents so that the teens can develop into young people who have insight. Smart and become the nations next formidable.Keywords : response, community, dimly lit cafe